Implementasi Sistem Informasi Pedidikan dan Latihan (SIDIKLAT) pada Instalasi Diklat RSUD dr. Chasbullah Abdulmadjid Kota Bekasi - Sanudin; Hadikristanto, Wahyu; Firmansyah, Andri; Edora; Purwanto (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
This training activity was conducted to enhance the capacity of the staff at the Education and Training Unit (Diklat) of RSUD dr. Chasbullah Abdulmadjid, Kota Bekasi, in operating and implementing the Education and Training Information System (SIDIKLAT). The training was designed to provide an in-depth understanding of the features and functions of SIDIKLAT that support the management of education and training at the hospital. The methods used included presentations, live demonstrations, and system simulations by the participants. During the training, participants were actively engaged in each session to ensure optimal technical and operational mastery. Evaluations showed that the training successfully improved the participants' competence in using SIDIKLAT and increased awareness of the importance of technology integration in education and training management. It is expected that after this training, the Diklat staff will effectively implement SIDIKLAT in their daily activities, thereby supporting the improvement of the quality and efficiency of education and training services at RSUD dr. Chasbullah Abdulmadjid.